Potensi Inhibitor Protein Non-struktural 1 (NS1) Berbasis Peptida untuk Mengobstruksi Replikasi Virus Dengue (DENV): Sebuah Kajian Literatur - Asyura, Muhammad Mikail Athif Zhafir; Fauzi, Ahmad; Ayub, Fakhru Adlan (Green Medical Journal, 2021)
Introduction: Dengue Virus (DENV) is the pathogen for human dengue fever and is responsible for 390 million infections per year. The viral genome produces about 10 viral protein products, one of them being NS1. The NS1 protein plays a key role in viral replication and stimulation of humoral immune cells, thus being the perfect candidate to create an effective antiviral drug or vaccine for dengue Methods: Dengue Virus (DENV) is the pathogen for human dengue fever and is responsible for 390 million infections per year. The viral genome produces about 10 viral protein products, one of them being NS1. The NS1 protein plays a key role in viral replication and stimulation of humoral immune cells, thus being the perfect candidate to create an effective antiviral drug or vaccine for dengue Conclusion: The review established promising results of using peptide-based intervention on NS1. Further in vivo and randomized controlled trials are advised to solidify the applicability and biosafety of the intervention